A viscosity model for fluorochloroindate glasses - Delben, JRJ; Delben, AAST; Oliveira, S. L.; Messaddeq, Younes [UNESP] (Elsevier B.V., 1999)
Viscosity of fluoride glasses is generally Arrhenian between glass transition temperature and crystallization temperature. This dependence on temperature is not observed in some special compositions which have two regions with different activation energies. The viscosity of glasses 40InF(3)-20ZnF(2)-25BaF(2)-10SrF(2)-5LiCl and 40InF(3)-20ZnF(2)-15SrF(2)-20BaF(2)-5NaCl was obtained by the parallel plate method. A theoretical model has been proposed to explain the viscosity data. (C) 1999 Elsevier B.V. B.V. All rights reserved.